Harnessing nature: a systematic exploration of in vitro antileishmanial and antihuman African trypanosomal properties in traditional medicinal plants and their active principles - Ahmed, Qamar Uddin; Mat Nasir, Nur Adlina; Begum, Taslima; Helal Uddin, A.B.M.; Parveen, Humaira; Albalawi, Mona O.; Khattak, Muhammad Muzaffar Ali Khan; Azmi, Syed Najmul Hejaz; Sarian, Murni Nazira; Kurniawati, Adelya Desi; Zakaria, Zainul Amiruddin (Taylor & Francis, 2026)
Context Current treatments for leishmaniasis and Human African Trypanosomiasis (HAT) are constrained by toxicity, high costs, and the growing threat of parasite resistance. In this context, natural products have emerged as promising alternatives, offering the potential for safer and more cost‑effective therapeutic interventions. Objective This review assesses the antileishmanial and antitrypanosomal activities of medicinal plants, underscoring their significance in addressing parasitic diseases and identifying promising candidates for future drug discovery and development. Methods Following the PRISMA 2020 guidelines, a systematic search was conducted for literature published between 2003 and 2023. Studies were considered eligible if they reported in vitro activities of extracts or compounds against Leishmania spp. or Trypanosoma brucei with IC50 < 10 µg/mL. Data included plant species, extraction methods, parasite strains, active compound(s), cytotoxicity profiles, and traditional uses. The quality of each study was evaluated based on the reproducibility of experimental procedures. Results and conclusions A total of fifty eligible articles were included. 217 plants demonstrated potent activity (IC₅。 < 10 µg/mL) against Leishmania spp. and/or T. brucei. Among these, 41 species had documented traditional use in the treatment of leishmaniasis or HAT, whereas 76 were traditionally employed for unrelated ailments yet exhibited scientific evidence of antiparasitic efficacy. Notably, 67 species were active against both parasites, 120 displayed selective antitrypanosomal, and 30 showed selective antileishmanial activities. Exemplary candidates include Achillea ptarmica L. (pellitorine), Allium sativum L. (allicin, ajoene), Strychnos spinosa Lam. (triterpenoids), Tridax procumbens L. (oxylipin), and Marrubium incanum Desr. (salvigenin). More studies should define mechanisms and in vivo efficacy.